2012
DOI: 10.1038/ja.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of desferrioxamine on bacterial growth and characteristics

Abstract: Desferrioxamines (DF's) are siderophores produced by some groups of bacteria. Previously, we discovered that DFE, produced by Streptomyces griseus, induced divergent developmental phenotypes in various Streptomyces isolates. In this study, we isolated bacteria whose phenotype was affected by the presence of 0.1 mM DFB from soil samples, and studied their phylogenetic position via 16 S rRNA gene-based analysis. Isolates belonging to Microbacterium grew only in the presence of DFB in the medium. DFB promoted gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…9 This was the first observation suggesting that in Streptomyces species, these ironchelating compounds might have a much more complex and subtle role in triggering a wide range of cellular processes. 6,9 In line with these findings, Tierrafria and collaborators showed that the disruption of the desferrioxamine-binding receptor encoded by desE resulted in loss of sporulation in S. coelicolor. 10 Recently, co-culture experiments demonstrated that iron competition through siderophore piracy between actinomycetes prevented S. coelicolor from entering its sporulation program.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…9 This was the first observation suggesting that in Streptomyces species, these ironchelating compounds might have a much more complex and subtle role in triggering a wide range of cellular processes. 6,9 In line with these findings, Tierrafria and collaborators showed that the disruption of the desferrioxamine-binding receptor encoded by desE resulted in loss of sporulation in S. coelicolor. 10 Recently, co-culture experiments demonstrated that iron competition through siderophore piracy between actinomycetes prevented S. coelicolor from entering its sporulation program.…”
Section: Introductionmentioning
confidence: 74%
“…2 This suggests that the survival of a large percentage of microorganisms on Earth may depend on neighbouring siderophore-producing species. 2 Iron plays essential roles in house-keeping functions such as DNA replication, protein synthesis and respiration, and siderophore-mediated iron uptake is specifically associated with many other biological processes such as fungal sexual development 3 and germination, 4 plant growth promotion, 5 pilus formation, 6 and pathogen virulence. 7,8 In a study by Ueda and colleagues on terrestrial antibiotic-producing streptomycetes, it was reported that morphological development (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cyclic AMP (cAMP), N-butyryl homoserine lactone, or N-oxohexanoyl-DL-homoserine lactone at a low concentration of 10 M permitted an increase in the microbial recovery of heterotrophic bacteria from the central Baltic Sea (146). The concept of mutualism between bacterial species emerged and was significantly highlighted by the role of siderophores (147)(148)(149). D'Onofrio et al identified 5 new acyldesferrioxamine siderophores isolated from Micrococcus luteus KLE1011, permitting the culture of a substantial number of marine bacterial species previously considered to be uncultivable (147).…”
Section: Signaling Compoundsmentioning
confidence: 99%
“…Furthermore, we performed screening for bacterial isolates with a desferrioxaminedependent phenotype and observed a stricter dependence of growth on the supply of desferrioxamine with regard to the isolates affiliated with Microbacterium. 25 In an isolate of Janthinobacterium lividum, treatment with desferrioxamine does not strongly affect the growth but stimulates the production of violacein, a purple pigment antibiotic. In contrast to the positive effect, growth of some bacteria is significantly inhibited due to the presence of desferrioxamine.…”
Section: Desferrioxaminesmentioning
confidence: 99%
“…In contrast to the positive effect, growth of some bacteria is significantly inhibited due to the presence of desferrioxamine. 25 This finding suggests that those bacteria do not retain the ability to use ferrioxamine but have a different ferric-ion uptake mechanism.…”
Section: Desferrioxaminesmentioning
confidence: 99%